1665 N.Y. Laws 205, Ordinance Of The Director General And Council Of New Netherland To Prevent Firing Of Guns, Planting May Poles And Other Irregularities Within This Province - (:unkn) unknown (General Publisher, 1665)
the director General and Council expressly forbid from this time forth all firing of Guns . . .on a penalty of 12 guilders for the first offense; double for the second offense, and for the third an arbitrary correction . . .
--
Keywords: DISCHARGE